Diet plasticity and links to changing foraging behaviour in the conservation of subantarctic yellow‐eyed penguins (Megadyptes antipodes). Issue 5 (12th March 2022) - Muller, Chris G.; Chilvers, B. Louise; French, Rebecca K.; Battley, Phil F.
Abstract: Diet is a key factor affecting seabird foraging behaviour, ultimately influencing survival, breeding success and long‐term population viability. The density and distribution of prey species in the marine environment are influenced by many factors including climate effects such as El Niño southern oscillation and climate change that alter water temperature. While poor quality diet has been implicated as a contributing factor in the decline of some mainland New Zealand yellow‐eyed penguin ( Megadyptes antipodes ) populations, little is known about their diet in the subantarctic where the majority of the species breeds. Blood and feather samples (n = 63) were collected for stable isotope analysis of diet from 25 individual birds breeding on subantarctic Enderby Island, Auckland Islands, New Zealand, from 2015 to 2018. Diet data were analysed by factors such as breeding year, sex and foraging behaviour. Stable isotope analysis demonstrated significant changes in diet during each year of the study, which included both El Niño and La Niña conditions. Diet during El Niño conditions comprised lower trophic level prey, which were more benthic, and found closer to shore than diet during La Niña. Coupled with the reported variable breeding success of yellow‐eyed penguins in the subantarctic, variable diet suggests prey availability is likely to be a limiting factor in some years. Prey availability is therefore expected to be a major influence on survival and breeding success of this endangered species in the future, particularly if the effects of climate change become more pronounced. This research highlights an urgent conservation need to identify prey species utilized by the southern population, along with their distribution in time and space, and therefore also the effect of diet on long‐term population stability.